Use of Skeletal Muscle Index as a Predictor of Wait‐List Mortality in Patients With End‐Stage Liver Disease. Issue 9 (6th August 2020) - Kappus, Matthew R.; Wegermann, Kara; Bozdogan, Erol; Patel, Yuval A.; Janas, Gemini; Shropshire, Erin; Parish, Alice; Niedzwiecki, Donna; Muir, Andrew J.; Bashir, Mustafa
Abstract : The aim of this study is to validate a proposed definition of sarcopenia in predicting wait‐list mortality. We retrospectively evaluated 355 adults (age ≥18 years) with cirrhosis listed for first‐time LT from January 1, 2010, to April 1, 2018 from our center. Demographic, laboratory, and outcome data were collected in conjunction with computed tomography scans performed within 3 months of listing. Using imaging analysis software, the skeletal muscle index (SMI), which is a marker for sarcopenia‐related mortality, was calculated. A survival analysis was performed to evaluate the association of the proposed sarcopenia definition of SMI <50 cm 2 /m 2 for men or <39 cm 2 /m 2 for women with wait‐list mortality or delisting. Median SMI was 54.1 cm 2 /m 2 (range, 47‐60 cm 2 /m 2 ). A total of 61 (17.2%) patients exhibited sarcopenia according to the proposed threshold, and 24.6% (57/232) of men were sarcopenic compared with 3.3% (4/123) of women ( P < 0.001). Mean (standard deviation [SD]) SMI was also higher for men (56.6 ± 9.6 cm 2 /m 2 ) than for women (50.7 ± 8.0 cm 2 /m 2 ; P < 0.001). Median follow‐up time among patients was 2.1 months (0‐12 months), and 30 events were observed (hazard ratio, 0.98; 95% confidence interval, 0.95‐1.02; P = 0.41). There was no statistically significant difference in time on the waiting list between patients with and without sarcopenia ( P = 0.89) as defined at the threshold. Using the prespecified definitions of sarcopenia based on SMI, there was no statistically significant difference in mortality and delisting from the transplant waiting list between patients with and without sarcopenia in this population. Practice and region‐specific patterns for pretransplant selection and median Model for End‐Stage Liver Disease at transplant may affect SMI as a predictor of wait‐list mortality.